Analysis of Pharmacists' Knowledge Level on Drug Management with The Availability of Medicine in Community Health Centers in Padang City - Juwita, Dian Ayu; Nasif, Hansen; Viviani, Ivana Regita (JSFK (Jurnal Sains Farmasi & Klinis), 2023)
The availability of medicine is one of the factors that can be employed to assess the quality of community health centers and determine customer satisfaction. Pharmacists require a strong foundation in drug management knowledge to ensure the medicine availability. Proficient drug management can enhance the rational use of medications, promote rational prescription practices, and improve drug utilization efficiency. This research aims to ascertain the pharmacist's knowledge level and the availability of medicine while also exploring any potential correlations between pharmacist knowledge and medicine availability. This research adopts a non-experimental study design with cross-sectional data collection. The research sample was selected using purposive sampling techniques, employing a questionnaire to assess pharmacist knowledge levels, as well as Drug Usage Reports and Drug Request Sheets (LPLPO) to evaluate the availability of medicine levels. Data analysis involved the Chi-Square test and Spearman Rank test. The study results indicated that the majority of pharmacists possessed a high level of knowledge (73.7%), while most community health centers have a moderate level of medicine availability (73.7%). The Spearman Rank test revealed no significant correlation between pharmacist knowledge levels and the availability of medicine.